Respuesta :

Answer:

4x - 3

Step-by-step explanation:

(7x - 2) - (3x - 5)

Open the bracket and observe the signs,

7x -2 - 3x + 5 ( when the minus outside the bracket multiplies minus in the bracket, it becomes plus)

Collect like terms

7x - 3x - 2 + 5

4x - 3

Answer:

4x + 3  is the answer obtained when we subtract (7x-2) - (3x-5)

Step-by-step explanation:

Given that, (7x-2)-(3x-5)  

Minuend = 7x-2

Subtrahend = 3x-5

In subtraction of algebraic terms, we place the variables together and the constants together and then perform the operation

Thus,  

= (7x-2)-(3x+5)  opening brackets and rewrite the equation.

= 7x-2-3x+5  bring 'x' terms together

= (7x-3x)-(2-5)

= 4x-(-3)

= 4x+3

Thus, after subtracting (7x-2)-(3x-5)  we get 4x+3